On the computability of the set of automorphisms of the unit square - Eike Neumann (Theoretical Computer Science, 2022)
We show that the closure of the set of orientation-preserving automorphisms of the unit square is computable in the bit-model of real computation. As an application we obtain a conditional result on the computability of the Fréchet-distance of continuous surfaces.